2019
DOI: 10.1155/2019/2309175
|View full text |Cite
|
Sign up to set email alerts
|

Maresin1 Alleviates Metabolic Dysfunction in Septic Mice: A 1H NMR-Based Metabolomics Analysis

Abstract: Maresin1 (MaR1), a new anti-inflammatory and proresolving lipid mediator, has been proven to exert organ-protective effects in septic animal models. However, the potential mechanisms are still not fully elucidated. In this study, we sought to explore the impact of MaR1 on metabolic dysfunction in cecal ligation and puncture- (CLP-) induced septic mice. We found that MaR1 significantly increased the overall survival rate and attenuated lung and liver injuries in septic mice. In addition, MaR1 markedly reduced t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 40 publications
0
24
0
Order By: Relevance
“…Fibrillar Aβ in plaques has been shown to stimulate microglia to secret pro-inflammatory cytokines, including IL-1, IL-6 and TNF-α (Murphy et al, 1998; Combs et al, 2001). There are reports indicating that MaR1 reduces TNF-α and IL-6 secretion in peripheral inflammation disease models such as septic mouse model (Hao et al, 2019), and human periodontal ligament cell model. In line with previous reports, we found MaR1 could reverse the increased levels of TNF-α and IL-6 induced by Aβ 42 in the central nervous system.…”
Section: Discussionmentioning
confidence: 99%
“…Fibrillar Aβ in plaques has been shown to stimulate microglia to secret pro-inflammatory cytokines, including IL-1, IL-6 and TNF-α (Murphy et al, 1998; Combs et al, 2001). There are reports indicating that MaR1 reduces TNF-α and IL-6 secretion in peripheral inflammation disease models such as septic mouse model (Hao et al, 2019), and human periodontal ligament cell model. In line with previous reports, we found MaR1 could reverse the increased levels of TNF-α and IL-6 induced by Aβ 42 in the central nervous system.…”
Section: Discussionmentioning
confidence: 99%
“…Previous study [21] reported that MaR1 could affect metabolic pathway in CLP-induced septic mice. They found that the levels of LDL/VLDL, glucose, isoleucine, and acetone levels were reduced in serum of CLP-induced septic mice.…”
Section: Discussionmentioning
confidence: 93%
“…Previous preclinical studies have reported that mice treated with MaR1 showed altered serum LDL/VLDL levels, and it also exerts potent anti-inflammatory and proresolution activities under both physiologic and disease conditions [9,21,22]. Thus, we assessed lipid-metabolic parameters and inflammatory factors in our subjects.…”
Section: Clinical and Laboratory Characteristics Of Studymentioning
confidence: 99%
“…For autophagy observation with electron microscope, lung tissues were fixed with glutaraldehyde. Resin-embedded lung tissue sections were cut at 50–70 nm thickness, stained with uranyl acetate and lead acetate, and then detected under a transmission electron microscope as previously described ( 24 ).…”
Section: Methodsmentioning
confidence: 99%